Non‐linear Stochastic Finite Element. Issue 1 (21st October 2015) - Caylak, Ismail; Dridger, Alex; Mahnken, Rolf
Abstract This paper investigates the uncertainty of physically non‐linear problems by modeling the elastic random material parameters as stochastic fields. For its stochastic discretization a polynomial chaos (PC) is used to expand the coefficients into deterministic and stochastic parts. Then, from experimental data for an adhesive material the distribution of the random variables, i.e. Young's modulus E(θ), the static yield point Y0 and the nonlinear hardening parameters q and b, are known. In the numerical example the distribution of the stresses obtained by the PC based SFEM and Monte Carlo simulation is compared. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)